2020
DOI: 10.1002/ece3.6106
|View full text |Cite
|
Sign up to set email alerts
|

Nightly selection of resting sites and group behavior reveal antipredator strategies in giraffe

Abstract: This study presents the first findings on nocturnal behavior patterns of wild Angolan giraffe. We characterized their nocturnal behavior and analyzed the influence of ecological factors such as group size, season, and habitat use. Giraffe were observed using night vision systems and thermal imaging cameras on Okapuka Ranch, Namibia. A total of 77 giraffe were observed during 24 nights over two distinct periods—July–August 2016 (dry season) and February–March 2017 (wet season). Photoperiod had a marked influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 69 publications
(136 reference statements)
1
23
0
Order By: Relevance
“…While zoos provide good conditions for observing and collecting data on nocturnal behavior, greater difficulties arise in the field (e.g., lack of information regarding age, biography and social relationships of the observed animals, unpredictability of encountering animals, high costs, etc.). Nevertheless, there are initial studies that have taken up these challenges and are using state‐of‐the‐art technology and innovative approaches to gain knowledge of the nocturnal behavior of wild large herbivores (e.g., Burger,Fennessy, et al, 2020; Davimes et al, 2018; Gravett et al, 2017; Pellew, 1984; Santymire et al, 2012). Among species, nocturnal activity budgets are quite diverse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While zoos provide good conditions for observing and collecting data on nocturnal behavior, greater difficulties arise in the field (e.g., lack of information regarding age, biography and social relationships of the observed animals, unpredictability of encountering animals, high costs, etc.). Nevertheless, there are initial studies that have taken up these challenges and are using state‐of‐the‐art technology and innovative approaches to gain knowledge of the nocturnal behavior of wild large herbivores (e.g., Burger,Fennessy, et al, 2020; Davimes et al, 2018; Gravett et al, 2017; Pellew, 1984; Santymire et al, 2012). Among species, nocturnal activity budgets are quite diverse.…”
Section: Introductionmentioning
confidence: 99%
“…Bashaw et al (2007) and Horova et al (2015) describe an adaptation to a herd structure in zoos where giraffe developed affiliative social bonds and dominance hierarchies. Furthermore, studies on African large herbivores showed a great variance in activity depending on season, temperature, habitat, vegetation, and food availability (Berger et al, 2003; Burger, Fennessy, et al, 2020; Deacon & Smit, 2017; Gravett et al, 2017). Understanding how various endogenous and exogenous factors affect the nocturnal activity and sleep behavior of captive giraffe was the aim of our research project.…”
Section: Introductionmentioning
confidence: 99%
“…An ability to determine sleep in a giraffe could be key for this species’ conservation [ 68 ]. During the phase of REM sleep a giraffe is fully unprotected [ 4 ] and the sleep duration can depict its stress exposure and be a response to a changing food quality/availability or to other stressors [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, where direct behavior observations of wild giraffes face restrictions caused by darkness or rough terrain, as in a recent study about the sleep of Angolan giraffes ( Giraffa camelopardalis angolensis) [ 68 ], the use of accelerometers is a helpful tool to observe giraffe behavior continuously. Combining different methods—such as recording the GPS location, acceleration data, conducting observations where possible—and different studies’ results can gather the needed information about the giraffe biology in order to protect and conserve the species.…”
Section: Discussionmentioning
confidence: 99%
“…In captive adult giraffe, a nocturnal recumbency bout lasts 2.5 h on average in both males and females, and individuals display a recumbent posture an average of 3.11 times per night (Takagi et al ., 2019). Wild giraffe also spend part of the night in a recumbent posture (Pellew, 1984; Burger et al ., 2020), but the characteristics of their diurnal recumbent behavior, such as duration or frequency, are poorly understood. Additionally, while habitat utilization has been studied in the contexts of feeding, herding, seasonality, and anthropogenic influences (Le Pendu & Ciofolo, 1999; Brand, 2007; Bercovitch & Berry, 2010 a ), little is known about the habitat utilization of wild giraffe for diurnal recumbent behavior.…”
Section: Introductionmentioning
confidence: 99%